2006
DOI: 10.1089/tmj.2006.12.571
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction Levels During Teleophthalmology Consultation in Rural South India

Abstract: The application of new technologies for analysis of retinal images, neural networks for automated retinopathy grading, and teleophthalmology have been shown to have great value in ophthalmology. India has only one ophthalmic surgeon for every 107,000 population. Given this situation, teleophthalmology can play a vital role in addressing to the eye care needs of the country. The objective of this study was to assess patient satisfaction levels and factors influencing it during teleophthalmology consultation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 23 publications
0
30
0
1
Order By: Relevance
“…When they assessed patient satisfaction levels during teleophthalmology consultation, it was reported that patients who asked questions during the screening were 2.18 times more likely to be satisfied with teleophthalmology than those who did not. 20 The Sankara Nethralaya experience is described in greater detail in another article in this symposium. The Aravind Comprehensive Eye Survey Research Group Study 18 showed that the prevalence of diabetic retinopathy in rural south Indian population using tele-ophthalmology was 10.5%.…”
Section: Tele-diabetology In Screening Diabetes and Associated Complimentioning
confidence: 99%
“…When they assessed patient satisfaction levels during teleophthalmology consultation, it was reported that patients who asked questions during the screening were 2.18 times more likely to be satisfied with teleophthalmology than those who did not. 20 The Sankara Nethralaya experience is described in greater detail in another article in this symposium. The Aravind Comprehensive Eye Survey Research Group Study 18 showed that the prevalence of diabetic retinopathy in rural south Indian population using tele-ophthalmology was 10.5%.…”
Section: Tele-diabetology In Screening Diabetes and Associated Complimentioning
confidence: 99%
“…Patient satisfaction with DR telemedicine varies widely from 35% to 99%. [27][28][29][30][31] But patient satisfaction does not measure patients' underlying beliefs. It is essential to engage patients to understand their attitudes, concerns, and perceptions before wide-scale implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies from around the world have also shown similar preferences for the use of teleophthalmology as screening tool for future ophthalmic screenings. Paul et al 19 in India found that 38% of patients found teleophthalmology more satisfying, whereas 60% felt that both models were equally satisfying.…”
Section: Telescreening: Are the Patients Satisfied?mentioning
confidence: 99%